Hidden Treasures: Precious Textiles from the St Eustace Head Reliquary - Joanne Dyer; Diego Tamburini; Naomi Speakman; Caroline R. Cartwright (Heritage, 2025)
Almost 70 years after the surprise discovery of a cache of textile-wrapped relics inside an early 13th-century reliquary bust, the St Eustace head reliquary (accession number 1850,1127.1), four of the textile relic wrappings were analysed by combining multiband imaging and fibre-optic reflectance spectroscopy (FORS), as well as dye analysis by high-pressure liquid chromatography coupled to mass spectrometry (HPLC-MS) and fibre analysis by scanning electron microscopy—energy dispersive X-ray spectroscopy (SEM-EDX). In all cases, the use of silk was confirmed, in line with the idea that these precious textiles were purposefully chosen for reuse in a sacred setting. Additionally, dye analysis was able to point to the possible geographic origins of the textile fragments. For 1850,1127.1.a, a mixture of sappanwood (Biancaea sappan) and flavonoid yellow dyes was commensurate with a Chinese or Central Asian origin. Mediterranean origins were thought likely for 1850,1127.1.c and 1850,1127.1.f, from the mixture of kermes (Kermes vermilio) and cochineal (likely Porphyrophora sp.), found in the mauve band of the former, and the combination of weld (Reseda luteola), madder (Rubia tinctorum) and an indigoid dye found in the latter. Finally, the unusual combination of sappanwood, orchil and a yellow dye containing flavonoid glucuronides suggested a less straightforward origin for textile 1850,1127.1.g. The other textile fragments from the reliquary were only investigated using FORS without removing them from their Perspex glass mounts. Nonetheless, indications for the presence of insect-red anthraquinone dyes, safflower (Carthamus tinctorius) and an indigoid dye were obtained from some of these fragments. The study provides a window into the landscape of availability, use and re-use in sacred contexts of precious textiles in the 13th century and evidences the geographic reach of these silks, allowing a new perspective on the St Eustace head reliquary.